ChemInform Abstract: Sodium Chlorate as a Viable Substoichiometric Oxidant for Cobalt‐Catalyzed Oxidative Annulation of Aryl Sulfonamides with Alkynes. Issue 47 (3rd November 2016) - Ran, You; Yang, Yudong; Zhang, Luoqiang
Abstract: For the first time, NaClO3 is demonstrated to be a versatile oxidant in the catalytic C—H activation of N‐(8‐quinolyl) substituted sulfonamides which react with alkynes to give sultams in good yields.